Porous Layer Characterization of Anodized and Black-Anodized Aluminium by Electrochemical Studies. (4th December 2012) - Franco, M.; Anoop, S.; Uma Rani, R.; Sharma, A. K.
Abstract : Three types of black anodic coatings, namely, black dyeing (BD), inorganic colouring (IC), and electrolytic colouring (EC) were prepared by conventional type II sulphuric acid anodizing on Al6061 alloys. Electrochemical behaviour of these coatings was studied by exposure to 3.5% wt sodium chloride solution for prolonged immersion periods up to 360 hours. The porous layer characteristics of all sealed, fresh and autosealed coatings were investigated by means of electrochemical impedance spectroscopy (EIS). An equivalent circuit that reproduces the a.c. impedance results of porous aluminium oxide films is proposed. The breakpoint frequency and damage function analysis were carried out to analyse the coating's electrochemical behaviour. Corrosion morphology was studied by scanning electron microscopy. It was observed that BD and IC behaved in a very similar manner to sulphuric acid anodising (SAA). However EC was behaving in an entirely different manner. Among all colouring methods BD was showing very less R p values. All these findings were further confirmed by linear polarisation studies. No major evidence of localised corrosion or pitting of the black anodic coatings was observed in SEM micrographs.